Analisis Perbandingan Financial Technology Pembayaran Digital Gopay Dan Ovo Terhadap Peningkatan Penjualan Umkm Kuliner Di Kota Bandung (Studi Pada GoFood dan GrabFood Partner) - Erlinda Astri Hapsari; Arif Afriady (Indonesian Accounting Literacy Journal, 2023)
This research was conducted in order to analyze the comparison of digital payment financial technology GoPay and OVO to increasing Culinary MSME sales in the city of Bandung. This research is a quantitative research using primary data. The population in this study are culinary SMEs in the city of Bandung. Sampling was carried out using the Lemeshow method with a total of 100 respondents. The data collection technique uses a questionnaire which is distributed to MSME actors with a scale of measurement using a Likert scale. The analytical method used is the Paired Sample t-test if the data meets the requirements for normally distributed data using the SPSS version 23 program. The results of this study indicate that there are differences in the use of GoPay and OVO digital payment financial technology for increasing sales at culinary MSMEs in the city of Bandung.